71=6(4n-8)-7n

Simple and best practice solution for 71=6(4n-8)-7n equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 71=6(4n-8)-7n equation:


Simplifying
71 = 6(4n + -8) + -7n

Reorder the terms:
71 = 6(-8 + 4n) + -7n
71 = (-8 * 6 + 4n * 6) + -7n
71 = (-48 + 24n) + -7n

Combine like terms: 24n + -7n = 17n
71 = -48 + 17n

Solving
71 = -48 + 17n

Solving for variable 'n'.

Move all terms containing n to the left, all other terms to the right.

Add '-17n' to each side of the equation.
71 + -17n = -48 + 17n + -17n

Combine like terms: 17n + -17n = 0
71 + -17n = -48 + 0
71 + -17n = -48

Add '-71' to each side of the equation.
71 + -71 + -17n = -48 + -71

Combine like terms: 71 + -71 = 0
0 + -17n = -48 + -71
-17n = -48 + -71

Combine like terms: -48 + -71 = -119
-17n = -119

Divide each side by '-17'.
n = 7

Simplifying
n = 7

See similar equations:

| 2(x-5)=3(x-1) | | s+6=78 | | 2x+3y-5x+5y= | | 5(1+6a)=-39+8a | | 2+2v=-2 | | 2z^3+9z^2=5z | | 5b-16-8n=-10 | | 7(y+1)=49 | | K=17 | | X+3=-32 | | 15-f=-23 | | 4-5(x+3)=25 | | -22+7r=6(r-4) | | 3x+7+6x+11=90 | | 4x+1=11x | | -2(5y+5)=4 | | 3*x=10 | | 8+16=-3(5x-8) | | 9(6x-5)=279 | | 22x-16x+12=-15+3x+12+6x | | 5x-9=13-x | | 7=20 | | 120*24= | | -30+5n=4+4(1+6n) | | -4(x+8)=-3x-5 | | 4(y+5)=-6(2y-1)+4y | | x^2+8x+8=o | | -5x=5x-100 | | 0.8x+.06(x+9)=1.24 | | 8w-33=-5(w+4) | | 102=-5(3-5m) | | -6=18k |

Equations solver categories